The role of moving images in the conference interpreting classroom - Rakhmawati, Susi Septaviana (Universitas Pendidikan Indonesia, 2016)
This paper reports on the study of the student interpreters’ performance in conference interpreting classes in an Indonesian university when multimodal texts were provided as part of the teaching methods. It aims to answer how multimodal texts can influence interpreting performance among students. A case study design was used to allow an in-depth analysis of the students’ interpreting performance as the phenomenon described (Yin, 2003) using triangulation of data analysis. Observation, interview, and seven transcription analysis from three students were carried out. Observation and interview result shows that the students used visual information such as lips movement, running text on video, moving images, and the speakers’ gestures in their interpreting processes. Moreover, the students said that the existing method of teaching interpreting using multimodal texts is really helpful for them in developing their interpreting skills. Furthermore, transcription analysis also confirms that the student with multimodal strategies (facing the speaker, the screen/the video) performed better during interpreting process. However, a student who faces both did not seem to perform well. The indication is that he was unable to focus, being distracted and nervous. Thus, overall the student interpreters used visual information as part of multimodal communication, in addition to speech, working on the regular mode of listening and speaking during interpreting process, which suggest significant contribution of multimodal texts to better rendition in the target language.